All that is solid melts into air : the experience of modernity - Berman, Marshall (London : Verso Books, 2010)
Marshall Berman's "All that is solid melts into air" is widely acclaimed as one of the greatest books on modernity. A kaleidoscopic journey into the experiences of modernization, the dizzying social changes that swept millions of people into the capitalist world, it dexterously interweaves an exploration of modernism in art, literature, and architecture.
Introduction: Modernity -- Yesterday, today and tomorrow -- 1. Goethe$1 (Bs Faust: the tragedy of development -- 2. All that is solid melts into air: Marx, modernism and modernization -- 3. Baudelaire: modernism in the streets -- 4. Petersburg: the modernism of underdevelopment -- 5. In the forest of symbols: some notes on modernism in New York.s
First published in the United States of America by Simon & Schuster, Inc., 1982 -- t.p. verso.
Includes bibliographical references and index
ARC
Keywords: Civilization, Modern -- 20th century; Civilization, Modern -- 19th century; Architecture